1992
DOI: 10.1007/bf00778997
|View full text |Cite
|
Sign up to set email alerts
|

Fat-induced changes in mouse pancreatic islet insulin secretion, insulin biosynthesis and glucose metabolism

Abstract: Insulin secretion, insulin biosynthesis and islet glucose oxidation were studied in pancreatic islets isolated from fat-fed diabetic mice of both sexes. Insulin secretion from isolated islets was studied after consecutive stimulation with alpha-ketoisocaproic acid + glutamine, glucose, forskolin, and 12-O-tetradecanoylphorbol 13-acetate. Glucose-induced insulin secretion was impaired in islets from fat-fed mice. This was associated with a reduction of approximately 50% in islet glucose oxidation. Islet insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
3

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 35 publications
3
30
0
3
Order By: Relevance
“…Investigation with isolated islets from 3-h lipid-infused rats show that the response to 27 mM glucose is enhanced, but after 48 h of intralipid infusion, the glucose-induced insulin release is reduced (Sako and Grill, 1990). Qualitatively, similar results have been observed in insulin secretory responses of humans with type 2 diabetes (Capito et al, 1992). Several studies (Prentki et al, 1992;Chen et al, 1994;Opara et al, 1994;Stein et al, 1997) have shown the importance of the type of FA on the process of glucose-induced insulin secretion in fed rats.…”
Section: Dietary Lipid Content and Insulin Secretionsupporting
confidence: 60%
“…Investigation with isolated islets from 3-h lipid-infused rats show that the response to 27 mM glucose is enhanced, but after 48 h of intralipid infusion, the glucose-induced insulin release is reduced (Sako and Grill, 1990). Qualitatively, similar results have been observed in insulin secretory responses of humans with type 2 diabetes (Capito et al, 1992). Several studies (Prentki et al, 1992;Chen et al, 1994;Opara et al, 1994;Stein et al, 1997) have shown the importance of the type of FA on the process of glucose-induced insulin secretion in fed rats.…”
Section: Dietary Lipid Content and Insulin Secretionsupporting
confidence: 60%
“…Possible mechanisms based on known modulatory effects of fatty acids include acylation [29], increased gene transcription [30], increased production of long chain-CoA products, or a direct effect of fatty acid metabolites on the enzyme activity. Regarding the latter, an inhibitory effect of long chain acyl-CoA esters has been reported for glucokinase [31,32], phosphofructokinase [33], and glucose 6-phosphatase [34]: we are not aware of any reports of stimulation of a glycolytic enzyme such as that noted in this study. No attempt to address these different possibilities was made in this study.…”
Section: Discussionmentioning
confidence: 58%
“…The similarity between fatty acids' effects on the insulin secretory response of isolated islets and the mechanisms underlying type 2 diabetes has been described [3,4]. The influence of free fatty acid (FFA) on insulin secretion is associated with the suppression of peripheral glucose uptake, stimulation of hepatic gluconeogenesis, defect in islet glucose recognition and fatty acid oxidation, as stated in the fuel concept and the Randle cycle hypothesis, the latter also known as the glucose-fatty acid cycle [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%